Reflection on compassion in Islam and Malay Sufi identity - Mohamad Nasrin Nasir, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Malays constitute around 300 million people in the Southeast Asian region. Historically many Malay Muslim scholar had practiced Sufism or tasawwuf in the past resulting in a rich heritage of writings on aspects of Sufism where many are still in Manuscript form. The lutfiyya (grace) of God or God’s breath (nafas al-rahman) is a constant feature in the worldview of the Sufis. God is seen to be an active principle in the world and human beings journey in this terrestrial world is in constant contact with God. Early formulation of Malay identity is forged with this in mind i.e. the everyday contact with God with the aim of reaching close to him. With the onslaught of colonialism such an identity is deviated from its original path. Instead various new needs are imposed upon that identity including the needs of the nation state. This has led to various results and growth of that identity. For better or for worse this paper argues that a return and an evolution to that early Sufi/inner-based identity with emphasis on compassion (al-rahman) is required for positive growth and development in the region.